Formative Assessment in Mathematics Learning: A Systematic Literature Review - Marlina Septiana; Elly Arliani; Kana Hidayati (Mandalika Mathematics and Educations Journal, 2026)
This study aims to critically examine the contribution of formative assessment to the processes and outcomes of mathematics learning through a Systematic Literature Review (SLR) approach. Ten scholarly articles published between 2015 and 2025 were analyzed based on rigorous inclusion criteria and selected from the ScienceDirect, ERIC, and Google Scholar databases. The findings indicate that formative assessment plays a significant role in enhancing student engagement, strengthening conceptual understanding, and supporting responsive teaching practices. Furthermore, formative assessment helps students reflect on their learning progress and promotes self-regulated learning in mathematics. Various forms of formative assessment have been identified, including technology-based interactive media, peer assessment, self-assessment, and visual and reflective feedback that encourage active student participation. However, the implementation of formative assessment faces several challenges, such as limited instructional time, digital literacy issues, teacher readiness, and technical difficulties in online learning environments. This review highlights the importance of continuous professional development for teachers and the establishment of a supportive assessment culture to ensure the effective implementation of formative assessment in mathematics education. The findings provide valuable insights for educators, researchers, and policymakers seeking to improve the quality of mathematics teaching and learning through evidence-based assessment practices.